Respuestas

2012-10-18T17:45:35+02:00

a)

     3            1            1

______  _ ____  =   _____

   X + 1         2           3X + 3

 

     3          1              1

______  _ ____  _   _____ = 0

   X + 1         2        3X + 3

 

3(6x+6) - (3x^2+6x+3) - (2x+2)

__________________________   = 0 

              (x+1)(6x+6)

 

     18x+18 - 3x^2-6x-3 - 2x-2

__________________________   = 0 

              (x+1)(6x+6)

 

             10x+13 - 3x^2

__________________________   = 0 

              (x+1)(6x+6)

 

            -(3x^2 - 10x - 13)

__________________________   = 0 

              (x+1)(6x+6)

 

             -(x+1)(3x-13)

__________________________   = 0 

              (x+1)(6x+6)

 

             -(3x-13)

__________________________   = 0 

              (6x+6)

 

            -(3x-13)

__________________________   = 0 

              2(x+3)

 

 

 

2012-10-18T17:48:37+02:00

a) (3/(x+1))-(1/2)=(1/(3x+3))

    (3/(x+1))-(1/2)=(1/(3(x+1)))

    (3/(x+1))-(1/(3(x+1)))=(1/2)

    (1/(x+1))*(3-(1/3))=(1/2)

    (1/(x+1))*(2/3)=(1/2)

    (1/(x+1))=(1/2)/(2/3)

    (1/(x+1))=(3/4)

    (x+1)=(4/3)

    x=(4/3)-1

    X=1/3

b) (4/(x-1))+(2/(x+1))=(35/((x^2)-1)) recordemos que los denominadores son los productos notables donde (x^2)-1=(x+1)*(x-1)

    (4*(x+1))/((x^2)-1)+(2*(x-1))/((x^2)-1)=(35/((x^2)-1))

    ((4x+4)+(2x-2))/((x^2)-1))=35/((x^2)-1))

    4x+4+2x-2=35

    6x+2=35

    6x=35-2

    6x=33

    x=33/6

    X=11/2